Treatment alternatives for anterior crossbite in the primary dentition. Report of two cases - Ramos Díaz, Laura; Hernandez Silva, Jesus Alberto (Revista Estomatología, 2025)
Anterior crossbite (ACB) in primary dentition is a malocclusion that is easily recognized by the general population and is a frequent reason for consultation. Once its etiology has been established, it must be treated in a timely manner to avoid alterations in the growth and functioning of the craniofacial complex. This malocclusion may have a dentoalveolar, functional, skeletal component or a combination. This article presents the importance of differential diagnosis in patients with ACB in primary dentition and shows treatment alternatives that are very well accepted by patients and have satisfactory therapeutic results.